How Bank Competition Affects Firms' Access to Finance - Love, Inessa; Martínez Pería, María Soledad (Published by Oxford University Press on behalf of the World Bank, 2017)
Using multi-year, firm-level surveys for 53 countries, this paper explores the impact of bank competition on firms’ access to finance. We find that low competition, as measured by high values on the Lerner index or Boone indicator, diminishes firms’ access to finance. In addition, the impact of competition on access to finance depends on the quality and scope of credit information sharing mechanisms, and better credit information mitigates the damaging impact of low competition. Overall, our paper offers consistent international evidence that supports the market power hypothesis, which argues that market power reduces access, and rejects the information hypothesis, which suggests that low competition improves access because it allows banks to internalize the investment in building firm-specific relationships.